ATTRIBUTES FOR THE FUNDAMENTAL REQUIREMENTS OF A GOOD PRACTICE OF ONLINE COURSE: A REFLECTIVE STUDY ON THE 1ST INDONESIAN MASSIVE OPEN ONLINE COURSE (IMOOC) - Hanung Triyoko; Muhamad Hasbi (English Department of Faculty of Tarbiyah and Teacher Training, 2018)
Technology advancement has allowed our education to make innovations, and massive open online courses (MOOCs) has become one of the promising programs that facilitate fruitful learning outcomes for many fields of study especially English language learning. This reflective study evaluated the first iteration of Indonesian Massive Open Online Course (IMOOC), in 2017, perceived from both facilitator and participant point of view, taking the IMOOC IAIN Salatiga camp as the sample subject of the study. Our reflections started with vignettes on challenges and opportunities for online learning and some attributes generally referred to as the basic requirements of successful open online course, such as, curiosity and richness in ways of the learning materials, preferences in learning and flexibility for the aspects of learning style and facilitation, and user-friendliness for the aspects of information and communication technology. Finally, our reflections as a facilitator and a participant to the first IMOOC discovered assorted technical and module-related issues faced by facilitator and participants respectively but both assured of opportunities prospective to develop professionalism in English language teaching in the future. In a more serious note, this study has formulated 3 attributes for the basic requirements of successful open online course namely providing multimodal contents in accordance with participant critical thinking level, accommodating different learning styles with stimulating facilitation, and utilizing current and user-friendly digital tools applicable and integrative in Indonesian teaching context.